1994
DOI: 10.1073/pnas.91.11.4791
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic synaptic modification threshold: computational model of experience-dependent plasticity in adult rat barrel cortex.

Abstract: Previous electrophysiological experiments have documented the response of neurons in the adult rat somatic sensory ("barrel") cortex to whisker movement after normal experience and after periods of experience with all but two whiskers trimmed close to the face (whisker "pairing9). To better understand how the barrel cortex adapts to changes in the flow of sensory activity, we have developed a computational model of a single representative barrel cell based on the Bienenstock, Cooper, and Munro (BCM) theory of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…A large body of research, dating back to the 1970s, has demonstrated experience and behavior-dependent plasticity in the adult rodent brain, especially with respect to synaptic structure (Diamond et al 1993;Benuskova et al 1994;Lebedev et al 2000). Kempermann et al found that, although neurogenesis decreased with increasing age, housing aged mice in an enriched environment led to increased survival of neuron progenitor cells (Kempermann et al 1998;Kempermann and Gage 1999a, b;Horner et al 2000;van Praag et al 2000).…”
Section: Brain Exercisementioning
confidence: 96%
“…A large body of research, dating back to the 1970s, has demonstrated experience and behavior-dependent plasticity in the adult rodent brain, especially with respect to synaptic structure (Diamond et al 1993;Benuskova et al 1994;Lebedev et al 2000). Kempermann et al found that, although neurogenesis decreased with increasing age, housing aged mice in an enriched environment led to increased survival of neuron progenitor cells (Kempermann et al 1998;Kempermann and Gage 1999a, b;Horner et al 2000;van Praag et al 2000).…”
Section: Brain Exercisementioning
confidence: 96%
“…BCM-like changes in plasticity induction account well for a variety of phenomena, including experience-dependent changes in visual and somatosensory neural activity (Benusková et al, 1994;Kirkwood et al, 1996;Philpot et al, 2003Philpot et al, , 2007 and synaptic plasticity in the dentate gyrus (Benuskova and Abraham, 2007). BCM-like metaplasticity effects over a shorter timescale have also been observed in the hippocampus, providing a tractable experimental preparation for testing the two key postulates noted above.…”
Section: Introductionmentioning
confidence: 99%
“…It was first examined in the visual system, where sensory experience could be altered and the subsequent effect on synaptic modification rules could be examined. Evidence for the sliding modification threshold was eventually obtained in multiple brain regions beyond the visual system [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%